Fishes of the Tambopata-Candamo reserved zone, southeastern Perú. - Chang, Fonchii (1998)
A list of fishes found in the Tambopata-Candamo Reserved Zone, Southeastern Peru is presented herein. This fauna includes 36 families, 138 genera and 232 species; characiforms and siluriforms are the main groups, dominating all environments. Faunal composition shows the general pattern found in other regions of the Amazon.